Role of magnetic nanoparticles incorporation for the enhanced efficiency of ZnO based Dye-Sensitized Solar Cells (DSSCs) - Abdallah, Noor; Abdullah, Basil A; Jabbar, Hashim (University of Thi-Qar Journal of Science, 2023)
In this study, we reported on the effect of the internal magnetic field arising from magnetic particles added to zinc oxide in certain proportions, which led to an improvement in the performance of the dye solar cell, We found that the magnetic effect It is the main factor that improves the ability to transfer electrons generated from the separation process between (electron-hole) pairs, And reduce the process of reunification between electrons and holes, The efficiency of the cell with a pure electrode was (1.38%), while the highest efficiency we got after doping was when doping with a ratio (97%ZnO+3%MnCoFeO4) reached (1.7%), i.e. the percentage increase in efficiency (23%).